Materializing Southeast Asia's past : selected papers from the 12th International Conference of the European Association of Southeast Asian Archaeologists. - Degroot, Veronique; Klokke, Marijke J. (NUS Press, 2013)
This book contains articles in historical and anthropological archaeology, epigraph, and art history. The interpretations of art and material culture offer understandings of classical Hindu and Buddhist cultures of Southeast Asia and their relationship to the region's medieval cultures. The articles are presented under four headings, as follows: art, religion and politics (Buddhist monuments in Java and Cambodia); Southeast Asian transformations (cultural exchange with South Asia); technology (workmanship in art and material culture); and Southeast Asia between past and present.